Midbrain Organoids: A New Tool to Investigate Parkinson’s Disease - Smits, Lisa Maria; Schwamborn, Jens Christian (Frontiers in Cell and Developmental Biology, 2020)
The study of human 3D cell culture models not only bridges the gap between traditional 2D in vitro experiments and in vivo animal models, it also addresses processes that cannot be recapitulated by either of these traditional models. Therefore, it offers an opportunity to better understand complex biology including brain development. The brain organoid technology provides a physiologically relevant context, which holds great potential for its application in modelling neurological diseases. Here, we compare different methods to obtain highly specialised structures that resemble specific features of the human midbrain. Regionally patterned neural stem cells were utilised to derive such human midbrain-specific organoids. The resulting neural tissue exhibited abundant neurons with midbrain dopaminergic neuron identity, as well as astroglia and oligodendrocyte differentiation. Within the midbrain organoids, neurite myelination and the formation of synaptic connections were observed. Regular neuronal fire patterning and neural network synchronicity were determined by multielectrode array recordings. In addition to electrophysiologically functional neurons producing and secreting dopamine, responsive neuronal subtypes, such as GABAergic and glutamatergic neurons were also detected. In order to model disorders like Parkinson’s disease in vitro, midbrain organoids carrying a disease specific mutation were derived and compared to healthy control organoids to investigate relevant neurodegenerative pathophysiology. In this way midbrain-specific organoids constitute a powerful tool for human-specific in vitro modelling of neurological disorders with a great potential to be utilised in advanced therapy development.